Detection of C‐Reactive Protein by Electrochemiluminescence‐Based Droplet‐Free Digital Immunoassay with Tyramide Signal Amplification - Hiroya Abe; Shuri Nakamura; Kentaro Ito; Kosuke Ino; Zhengyi Liu; Shinichi Sato; Kumi Y. Inoue; Hitoshi Shiku (ChemElectroChem)
C‐reactive protein (CRP) is a widely used biomarker for monitoring inflammatory processes and assessing disease progression in various conditions, including cardiovascular diseases, infections, and autoimmune disorders. In this study, a simplified droplet‐free digital enzyme‐linked immunosorbent assay (ELISA) system is developed based on electrochemiluminescence (ECL) imaging for the sensitive detection of CRP. This system eliminates the need for droplet or microwell arrays, significantly simplifying the workflow while maintaining high sensitivity. Tyramide signal amplification was employed to enhance signal generation, relying on its localized reaction to achieve precise single‐particle amplification with minimal signal diffusion. The developed assay is capable of detecting poly‐horseradish peroidase at concentrations as low as 1.0 fmol L−1 and successfully adhered to the Poisson distribution model for digital quantification. The application of this system to CRP detection yields a limit of detection of 17.0 pg mL−1 (162 fmol L−1). The ECL bead ratio increases proportionally with CRP concentration, enabling accurate quantification. Moreover, the system exhibits high specificity, showing no response to other biomolecules and maintaining precise detection even in complex biological samples such as human serum. This study highlights the potential of the droplet‐free digital ELISA system for clinical diagnostics and the detection of low‐abundance biomarkers.